2019
DOI: 10.1002/ps.5461
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the sensitivity of Plasmopara viticola to amisulbrom and ametoctradin in French vineyards using bioassays and molecular tools

Abstract: BACKGROUND: Complex III inhibitors are key compounds in the control of Plasmopara viticola. They are prone to the development of resistance, as demonstrated by the emergence of resistance to quinone-outside inhibitors. By using a combination of bioassays and molecular methods, we monitored sensitivity to amisulbrom and ametoctradin in P. viticola populations in French vineyards from 2012 to 2017. RESULTS:We found that the alternative oxidase (AOX)-related resistance mechanism was common in French P. viticola p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
64
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(72 citation statements)
references
References 34 publications
8
64
0
Order By: Relevance
“…Further spectroscopic studies indicated that the compound could target both Q o and Q i sites [31] and the fungicide was re‐classified as QioI (https://osf.io/qwg42/). However, the appearance of the ametoctradin resistance mutation S34L in the Q i site of Plasmopara viticola ‐resistant isolates showed that the fungicide preferentially targets the Q i site, which was confirmed by the study of the mutation in the yeast model [51,65]. Analysis of in silico docking of ametoctradin into a homology model of the Q i site of Plasmopara viticola suggests a binding mode similar to that of ubiquinol in yeast cyt bc 1 .…”
Section: Qii Fungicides In Use and Under Development And Appearance mentioning
confidence: 93%
See 3 more Smart Citations
“…Further spectroscopic studies indicated that the compound could target both Q o and Q i sites [31] and the fungicide was re‐classified as QioI (https://osf.io/qwg42/). However, the appearance of the ametoctradin resistance mutation S34L in the Q i site of Plasmopara viticola ‐resistant isolates showed that the fungicide preferentially targets the Q i site, which was confirmed by the study of the mutation in the yeast model [51,65]. Analysis of in silico docking of ametoctradin into a homology model of the Q i site of Plasmopara viticola suggests a binding mode similar to that of ubiquinol in yeast cyt bc 1 .…”
Section: Qii Fungicides In Use and Under Development And Appearance mentioning
confidence: 93%
“…This represents a significant decrease from the 10H + /2e − yield expected for cyt bc 1 /cytochrome c oxidase‐linked respiration. Putatively AOX‐linked fungicide resistance was first noted in laboratory‐generated strains of Z. tritici , that were resistant to the (then) newly developed QoI azoxystrobin [77], and has subsequently has been observed in QoI/QiI‐treated field isolates of the phytopathogens Plasmopara viticola , Z. tritici , Magnaporthe grisea and Mycosphaerella fijensis [65,78–80]. In vitro studies suggest that, in the absence of selective pressure, AOX overexpression in Plasmopara viticola sporangia comes with an associated fitness penalty [6], presumably due to the decreased energetic efficiency of mitochondrial respiration as outlined above.…”
Section: Alternative Qoi/qii Resistance Mechanisms In Fungal Phytopatmentioning
confidence: 99%
See 2 more Smart Citations
“…Downey mildew symptoms are characterised by initial yellow and oily spots on leaves and other green parts of the plant that evolve in necrosis and death of infected tissues, including bunches, possibly resulting in a total crop loss 4 . In order to control the disease, several fungicide treatments, including the copper (Cu)-based ones, are commonly applied in vineyards 3 , 5 , 6 . However, there are growing concerns about the possible negative impact of synthetic chemical fungicides and Cu on human health and the environment 7 9 .…”
Section: Introductionmentioning
confidence: 99%